2014
DOI: 10.1177/1687814020960630
|View full text |Cite
|
Sign up to set email alerts
|

Study on the influence of blade outlet cutting on hydraulic noise of centrifugal pump with low specific speed

Abstract: In order to study the influence of blade outlet cutting width on hydrodynamic excitation noise of the centrifugal pump with low specific speed, five schemes are used to perform V-shaped cutting on the outlet of the impeller blade are studied in this study. Based on Lighthill acoustic analogy, combining computational fluid dynamics and computational acoustics, RNG k-ε turbulence model is used to calculate internal unsteady flow field of the centrifugal pump, and the acoustic solution is based on the flow field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…The noise source of the FW-H equation in the dipole source term is related to the pressure pulsation. Some scholars believe that the strongest point of pressure pulsation inside the hydraulic turbine occurs at the volute tongue, so it is particularly important to analyze the induced noise of the hydraulic turbine of the pressure pulsation at the volute tongue [22]. In the unsteady calculation of the flow field, the monitoring point P1 is located at the tongue of the volute spacer, as shown in Fig.…”
Section: Analysis Of Unsteady Results Of Flow Field Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The noise source of the FW-H equation in the dipole source term is related to the pressure pulsation. Some scholars believe that the strongest point of pressure pulsation inside the hydraulic turbine occurs at the volute tongue, so it is particularly important to analyze the induced noise of the hydraulic turbine of the pressure pulsation at the volute tongue [22]. In the unsteady calculation of the flow field, the monitoring point P1 is located at the tongue of the volute spacer, as shown in Fig.…”
Section: Analysis Of Unsteady Results Of Flow Field Calculationsmentioning
confidence: 99%
“…As a typical rotating machinery, research on the vibration and noise of centrifugal pumps has been fruitful at home and abroad [5][6][7][8][9]. Cheng et al [10] improved the noise of a centrifugal pump by cutting the outlet side of the impeller, and found that there exists an optimal cutting width to weaken the rotorstator interaction between the impeller and the volute, which effectively reduces its internal and external sound field. To study the mechanism of noise induced by unstable flow inside a centrifugal pump, Lu et al [11] analyzed it through a combination of experiments and numerical simulations and found that the noise could effectively react to the phenomena of flow stall and instability inside the pumps.…”
Section: Introductionmentioning
confidence: 99%
“…It was showed that the noise decreased first, then increased with the increase of blade number. Cheng et al [20] investigated the impact of blade outlet cutting on the noise at pump inlet and outlet. The results showed that the V-shaped cutting improved the noise performance.…”
Section: Introductionmentioning
confidence: 99%